A Cognitive Construction Grammar approach to the pluralization of presentational haber in Puerto Rican Spanish. (16th June 2014) - Claes, Jeroen
Abstract In this paper, I present an analysis of the pluralization of haber 'there is/are' in Puerto Rican Spanish (e.g., habían fiestas 'there were parties') as an ongoing language change from below in which the impersonal argument-structure construction (<AdvPhaberObj>) is being replaced by a personal variant (<AdvPhaberSubj>). Speakers pluralize presentational haber in about 41% of the cases, and linguistic conditioning factors are 'typical action chain-position of the noun's referent, ' polarity of the clause, verb tense, comprehension-to-production priming, and production-to-production priming. I argue that the effect of these independent variables can be traced back to three cognitive factors: the preference for unmarked coding, statistical preemption, and structural priming. Social distributions can also be modeled in constructionist frameworks, with results for social class, formality, and gender advocating in favor of considering this variation as an ongoing change from below, which allows speakers to position themselves in terms of gender and social class.